Association of a P2RX7 gene missense variant with brachycephalic dog breeds. (27th November 2019) - Sophocleous, R. A.; Sluyter, V.; Curtis, B. L.; Curtis, S. J.; Jurak, L. M.; Faulks, M.; Spildrejorde, M.; Gates, S.; Proctor, E.‐J.; Seavers, A.; Watson, D.; Kuit, T.; et al.
Summary: Missense variants are associated with various phenotypic traits and disorders in dogs. The canine P2RX7 gene, coding the ATP‐gated P2X7 receptor ion channel, contains four known missense variants. The current study aimed to examine the presence of these variants in a random sample of pedigree and mixed‐pedigree dogs. Exons 3, 8, 11 and 13 of the P2RX7 gene, encoding these four respective variants, in 65 dogs were assessed by Sanger sequencing and combined with existing sequencing data from another 69 dogs. The distribution of these variants was then evaluated in all 134 dogs combined and separately within individual breeds including 35 different pure breeds. The rs23314713 (p.Phe103Leu) and rs23315462 (p.Pro452Ser) variants were present in 47 and 40% of all dogs studied respectively, with the rs23314713 variant associated with brachycephalic breeds. Among pedigree dogs, the rs23314713 and rs23315462 variants were associated with brachycephalic and non‐brachycephalic breeds respectively. The rs851148233 (p.Arg270Cys) and rs850760787 (p.Arg365Gln) variants were present only in dogs of Cocker Spaniel and Labrador Retriever pedigrees respectively. No other missense variants were found in exons 3, 8, 11 and 13 of the P2RX7 gene within the dogs. In conclusion, the rs23314713 and rs23315462 missense variants of the P2RX7 gene are present in a large proportion of dogs, with the rs23314713 variant associated with a number of brachycephalic breeds. However, the association of this variant with dogs of bulldog ancestry, not brachycephaly per se, cannot be excluded.